(untitled) (Research, Society and Development, 2023)
This article aims to verify the conceptions of mathematics teachers in Basic Education about the formalization and relationship of mathematical knowledge with other disciplines and the social context. The qualitative research was carried out in the field, using the interview as an instrument to collect the conceptions of ten (10) mathematics teachers from the Final Years and High School of public and private schools in Paraíba. After the data obtained, transcripts were made for the necessary analyzes and theoretical discussion based on Bardin’s content analysis. With the results, we realized that the questions asked to the research teachers about mathematical knowledge, provided opportunities for reflection, as some had difficulties in relating mathematics to other contexts. Teachers must follow a continuous process of reflection and action, in order to consolidate or change perceptions that influence daily actions and pedagogical practice carried out in the classroom. Continuing education is fundamental to remedy the gaps in teachers’ initial training and improve specific and pedagogical knowledge, offering students the construction of mathematical knowledge that goes beyond the cognitive dimension and prepares students to act critically, consciously, autonomously and democracy in society.